The mental health of medicine students: an integrative review (Research, Society and Development, 2023)
Mental health refers to a well-being in the individual to develop their personal skills, manage with the stress of life, work productively and be able to make their contribution to their community. That said, note that medical courses associated with mental health are increasingly increasing within the treatment space. Thus, this work aims to bring a more detailed look at the mental health of medical students, how mental disorders and health promotion for students is being done, in addition to the consequences of such disorders for the student's life. of medicine. For this, an integrative review of data from 2022 was carried out, always opting for the most recent, in order to compare and extract the newest and most evaluated data. Every one medical student has a prevalence rate that is higher than the general population, when looking at as medical students, they are also among medical students. In addition, most medical students said they self-medicate, citing drugs of various classes including hypnotics, anxiolytics and antidepressants, which can lead to serious consequences. In this way, it is concluded that it is extremely important to understand the profile of these students, and that universities take actions that see a hostile and more integrative environment in order to improve mental health rates among these students.